A user-centered design and analysis of an electrostatic haptic touchscreen system for students with visual impairments. Issue 109 (January 2018) - Bateman, Amelia; Zhao, Oliver K.; Bajcsy, Andrea V.; Jennings, Mathew C.; Toth, Bryan N.; Cohen, Alexa J.; Horton, Emily L.; Khattar, Anish; Kuo, Ryan S.; Lee, Felix A.; Lim, Meilin K.; Migasiuk, Laura W.; et al.
Highlights: Electrostatic haptic touchscreen for displaying graphs to users with visual impairments. 12 participants with visual impairments tested usability via a dot localization task. Increase in task accuracy indicates rapid improvement in detection of haptic objects. Effective and ineffective screen exploration strategies discovered. Implications for future multimodal assistive device design. Abstract: Students who are visually impaired face unique challenges when learning mathematical concepts due to the visual nature of graphs, charts, tables, and plots. While touchscreens have been explored as a means to assist people with visual impairments in learning mathematical concepts, many devices are not standalone, were not developed with a user-centered design approach, and have not been tested with users who are visually impaired. This research details the user-centered design and analysis of an electrostatic touchscreen system for displaying graph-based visual information to individuals who are visually impaired. Feedback from users and experts within the visually-impaired community informed the iterative development of our software. We conducted a usability study consisting of locating haptic points in order to test the efficacy and efficiency of the system and to determine patterns of user interactions with the touchscreen. The results showed that: (1) participants correctly located haptic points with an accuracy rate of 69.83% and an average time of 15.34 s out of 116 total trials, (2) accuracy increased across trials, (3) efficient patterns of user interaction involved either a systematic approach or a rapid exploration of the screen, and (4) haptic elements placed near the corners of the screen were more easily located. Our user-centered design approach resulted in an intuitive interface for people with visual impairments and laid the foundation for demonstrating this device's potential to depict mathematical data shown in graphs.